Tonsillar carcinoma as a rare cause of cardiac metastases - Princess Mark-Adjeli (Journal of Community Hospital Internal Medicine Perspectives, 2019)
Tonsillar carcinoma metastasis to the myocardium is undermined with detection rate often occurring at autopsy or advance stage. A 60-year-old male with a 1-month history of right-sided facial pain and failed antibiotics therapy underwent head and neck CT scan that revealed a tonsillar mass. Tonsillar biopsy revealed squamous cell carcinoma, HPV-16 positive. PET-CT scan showed a significant activity in the right tonsillar mass along with prominent right level 2 lymph nodes and no distant disease. Definite surgery was deferred and he underwent 7 weeks of radiation therapy with concurrent weekly Cisplatin. PET scan 8 weeks later showed significant improvement in large right palatine tonsil mass; however, a new FDG-avid cardiac mass of right ventricle. An echocardiogram showed an ejection fraction of 59% and a large mass in the apical portion of the right ventricle. Cardiac MRI confirmed a 9 cm right ventricular mass. Complete resection of the cardiac mass was unsuccessful; a partial tumor debulking provided adequate sample for pathologic examination, which was consistent with metastatic squamous cell cancer, p16+, clinical-stage T4aN1M1. Surgical intervention was not performed; instead, he received a palliative radiation therapy to his right-sided cardiac mass with concurrent Keytruda immunotherapy. Unfortunately, the evening of successfully completing his last therapy, he was found unresponsive and subsequently expired. Although tonsillar carcinoma metastasis to the myocardium is rarely coupled with its atypical presentations, clinicians should consider early echocardiogram evaluation for possible metastatic disease so as to provide early interventions.